2021
DOI: 10.1097/ccm.0000000000005034
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Premorbid Beta-Blocker Exposure and Sepsis Outcomes—The Beta-Blockers in European and Australian/American Septic Patients (BEAST) Study

Abstract: OBJECTIVES: To examine the effect of premorbid β-blocker exposure on mortality and organ dysfunction in sepsis. DESIGN: Retrospective observational study. SETTING: ICUs in Australia, the Czech Republic, and the United States. PATIENTS: Total of 4,086 critical care patients above 18 years old with sepsis between January 2014 and December 2018. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 50 publications
1
20
1
Order By: Relevance
“…Liu et al [26] conjecture that downregulation of beta-receptors in sepsis may attenuate the increase in CI caused by dobutamine and suggest that, while the dose of dobutamine used in the studies they identified (5 μg/kg/min) may therefore be insufficient in this setting, any higher dose may come with an increased risk of cardiac arrhythmias. We also note data indicating a survival benefit from beta-blockers in sepsis [32,33]; this implies an adverse impact of betaadrenergic activity on survival in sepsis that might be addressed (at least in part) by avoiding dobutamine and reducing noradrenaline in favour of levosimendan.…”
Section: Expertsʼ Assessmentmentioning
confidence: 87%
“…Liu et al [26] conjecture that downregulation of beta-receptors in sepsis may attenuate the increase in CI caused by dobutamine and suggest that, while the dose of dobutamine used in the studies they identified (5 μg/kg/min) may therefore be insufficient in this setting, any higher dose may come with an increased risk of cardiac arrhythmias. We also note data indicating a survival benefit from beta-blockers in sepsis [32,33]; this implies an adverse impact of betaadrenergic activity on survival in sepsis that might be addressed (at least in part) by avoiding dobutamine and reducing noradrenaline in favour of levosimendan.…”
Section: Expertsʼ Assessmentmentioning
confidence: 87%
“…Use of β-blockers was associated with a reduced risk of critical COVID-19 but not influenza in our study. Premorbid use of β-blockers has been associated with improved outcomes in sepsis ( 50 ), and recently, a small randomized study showed that inhospital treatment with metoprolol improved gas exchange in COVID-19–induced ARDS ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…Five observational studies have assessed the effect of pre-morbid beta-blockade on lactate levels in patients presenting with sepsis 39 43 . Three trials found a significant reduction in lactate levels with beta-blockade 39 , 41 , 43 , while two showed no difference 40 , 42 . A recent meta-analysis of these studeis found lactate levels to be lower in patients on beta-blockers 44 .…”
Section: Introductionmentioning
confidence: 94%